2016
DOI: 10.1063/1.4950860
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of imaging plates to electrons between 40 and 180 MeV

Abstract: This paper presents the response calibration of Imaging Plates (IPs) for electrons in the 40-180 MeV range using laser-accelerated electrons at Laboratoire d'Optique Appliquée (LOA), Palaiseau, France. In the calibration process, the energy spectrum and charge of electron beams are measured by an independent system composed of a magnetic spectrometer and a Lanex scintillator screen used as a calibrated reference detector. It is possible to insert IPs of different types or stacks of IPs in this spectrometer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…The spectrometers used BAS-MS image plate (IP) detectors scanned using a GE Typhoon FLA 7000 scanner. The raw signal of the image plates (Figure 2) was converted to total electron number using the method described by Tanaka, et al [49] with the IP calibration given by Rabhi, et al [50] For comparison shots, we used a standard 2 m flat Cu target and a 300 m flat glass target. The latter was cut from the edge of the MCP where no channels were present to have a material matching that of the channel walls.…”
Section: A Experimentsmentioning
confidence: 99%
“…The spectrometers used BAS-MS image plate (IP) detectors scanned using a GE Typhoon FLA 7000 scanner. The raw signal of the image plates (Figure 2) was converted to total electron number using the method described by Tanaka, et al [49] with the IP calibration given by Rabhi, et al [50] For comparison shots, we used a standard 2 m flat Cu target and a 300 m flat glass target. The latter was cut from the edge of the MCP where no channels were present to have a material matching that of the channel walls.…”
Section: A Experimentsmentioning
confidence: 99%
“…Nevertheless, the response of the scintillator is energy dependent and the energy resolution cannot be maximized due to the fabrication limits on the smallest size of the scintillator. On the other hand, the Imaging Plates (IPs) are well calibrated over the wide range of energy spectrum compared to the scintillators; [24][25][26] they also offer high resolution and dynamic range, are unsensitive to electromagnetic pulses, durable and cost effective. 13,14,24,26 In addition, they are flexible and can easily move along a guided groove of plane 1 with no compromise in the detection of a particle beam with continuous energy range.…”
Section: Detection Challenges and Optionsmentioning
confidence: 99%
“…On the other hand, the Imaging Plates (IPs) are well calibrated over the wide range of energy spectrum compared to the scintillators; [24][25][26] they also offer high resolution and dynamic range, are unsensitive to electromagnetic pulses, durable and cost effective. 13,14,24,26 In addition, they are flexible and can easily move along a guided groove of plane 1 with no compromise in the detection of a particle beam with continuous energy range. Even though the gradient magnet design offers nice feature of focusing effect for a horizontally spread beam, the acceptance of the gradient magnet is limited by the fact that the transverse spatial profile of a practical beam has both horizontal and vertical distribution.…”
Section: Detection Challenges and Optionsmentioning
confidence: 99%
“…Researchers have measured the response of IPs to various radiation types such as electrons [5,7,13,[17][18][19][20][21], protons [12,14,[22][23][24], and X-ray [16,25] for a wide energy range. The measurement of IP responses to energetic heavy ion beams, however, is more challenging because it is difficult to produce heavy ion beams with sufficient particle fluence for IP calibration at a range of energies in a reasonably short time.…”
Section: Introductionmentioning
confidence: 99%
“…Bonnet et al designed an exponential model and calibrated the IP response to protons, electrons, photons, and 4 He ions, using Geant4 [14,16,29]. Recently, Rabhi et al reported on the responses of BAS-MS, SR, and TR for 1-200 MeV protons [12] and for 40-180 MeV electrons [21] using Geant4. Singh et al used FLUKA to calibrate the responses of BAS-MS and SR to 150 keV-1.75 MeV electrons [5].…”
Section: Introductionmentioning
confidence: 99%